The role of the inhomogeneous demagnetizing field on the reversal mechanism in nanowire arrays. (31st October 2017) - Vock, S; Hengst, C; Sasvári, Z; Schäfer, R; Schultz, L; Neu, V
Abstract: The magnetization behavior of nanowires arranged in an array is strongly influenced by the strength and shape of the demagnetizing field experienced by the individual nanowires. In order to understand the initial stage of the reversal process in nanowire arrays a hybrid method is proposed. First, an expression for the numerical calculation of the demagnetizing field in nanowire arrays is presented and compared to already available approaches. The derived expression calculates the demagnetizing field as a function of position along the length of an individual nanowire embedded in the array. In a second step, a micromagnetic simulation of the reversal process of a an isolated nanowire (1 μ m) is superimposed with the earlier obtained field distribution. This enables including the inhomogeneity of the demagnetizing field of a large array (≈10 8 nanowires) into the micromagnetic simulation without the need of particularly large computing power. The simulation results show that in contrast to the switching in a single nanowire, where the reversal starts at the nanowire ends, the reversal under the influence of the array field strongly depends on the magnetization state of the whole array. Reversal can start either at the nanowire's central region or at its ends.